2001
DOI: 10.1023/a:1012414119944
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of DMBA-induced mammary cancer in rats by dietary soy

Abstract: This study was designed to assess the potential chemopreventive effect of the administration of a standardized soy extract, SOYSELECT, on 7,12-Dimethylbenz[a]anthracene (DMBA)-induced mammary tumors in rats. Three groups, 24 females each, were used. Animals were fed either a phytoestrogen-free diet alone (control) or the same diet supplemented with 0.35% or 0.7% of soy extract. Treatment started at weaning and continued to the end of the study (24 weeks after DMBA administration). At day 50 of age all animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…In contrast to the results of these studies, dietary feeding of supraphysiological concentrations of daidzein to female rats neither caused significant toxicity to the reproductive tract nor provided protection against chemically induced mammary cancer (107). In studies in which rats were fed a standardized soy extract instead of pure isoflavone, chemically induced mammary adenocarcinomas took longer to develop than in control animals, but at the end of the study no difference in tumor multiplicity or incidence was observed between treatment and controls (62).…”
Section: Potential Health Beneficial Effects Of Isoflavonoid Phytoestcontrasting
confidence: 64%
“…In contrast to the results of these studies, dietary feeding of supraphysiological concentrations of daidzein to female rats neither caused significant toxicity to the reproductive tract nor provided protection against chemically induced mammary cancer (107). In studies in which rats were fed a standardized soy extract instead of pure isoflavone, chemically induced mammary adenocarcinomas took longer to develop than in control animals, but at the end of the study no difference in tumor multiplicity or incidence was observed between treatment and controls (62).…”
Section: Potential Health Beneficial Effects Of Isoflavonoid Phytoestcontrasting
confidence: 64%
“…Only one of the five studies that exposed rats to genistein or SPI found any effect on mammary tumour incidence or multiplicity (Constantinou et al, 2001), and two studies reported a longer tumour latency (Constantinou et al, 2001;Gallo et al, 2001). The study of Constantinou et al (2001) found that an exposure to SPI that was depleted of IFs had the most significant effect on tumour latency and multiplicity.…”
Section: Ratsmentioning
confidence: 99%
“…On the other hand, in a large cohort study of British women no effects of dietary isoflavone intake and breast cancer risk were found among either pre-or post-menopausal women (10). Experimental studies showed variable results on breast cancer reduction by soy or the soy isoflavone genistein (11)(12)(13)(14)(15). For example, it was reported that genistein reduces the growth of tumors that arise from inoculated human or mouse breast cancer carcinoma cells in pre-menopausal mouse models (16,17).…”
Section: Introductionmentioning
confidence: 99%